Torque Characteristic Analysis of Outer Rotor Permanent Magnet Generator for Low Head Hydro Power Application - Pudji Irasari; Muhammad Fathul Hikmawan; Puji Widiyanto (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2019)
This paper analyzes the torque characteristics of outer rotor PMG for low head hydro power application. The aim is to prevent the generator torque from exceeding the turbine torque as the prime mover so that the system can work properly in both start and steady state conditions. The PMG is of outer rotor type and the torques are calculated analytically and numerically. The analysis is focused only on the PMG without connecting it to the turbine. Two analyzed torques include electromagnetic torque and starting torque, which comprises cogging torque, hysteresis torque and friction torque. The electromagnetic torque was obtained by loading the PMG with resistance and impedance (RL-LL in series) respectively. The results indicate that electromagnetic torque is the highest among all the investigated torques although its value is only 5.6% of the turbine torque, and cogging torque is the highest among the starting torque. From those results, it can be concluded that the hydro turbine torque can overcome the generator torque both at start and steady state conditions.